2007
DOI: 10.1111/j.1532-5415.2007.01358.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐Intensity Environmental Light in Dementia: Effect on Sleep and Activity

Abstract: Bright light appears to have a modest but measurable effect on sleep in this population, and ambient light may be preferable to stationary devices such as light boxes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
116
2
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(130 citation statements)
references
References 32 publications
6
116
2
6
Order By: Relevance
“…Figueiro et al [47,48], van Someren et al [45], Sloane et al [52] and Riemersma-van der Lek [53], demonstrated that light of the right spectrum and of sufficient amount applied at the proper circadian time can positively impact sleep efficiency and sleep consolidation in older adults, including those with AD. The present results are also consistent with the knowledge that the circadian system is maximally sensitive to short wavelength radiation (blue light) and minimally sensitive to long wavelength radiation (yellow and red).…”
Section: Discussionmentioning
confidence: 99%
“…Figueiro et al [47,48], van Someren et al [45], Sloane et al [52] and Riemersma-van der Lek [53], demonstrated that light of the right spectrum and of sufficient amount applied at the proper circadian time can positively impact sleep efficiency and sleep consolidation in older adults, including those with AD. The present results are also consistent with the knowledge that the circadian system is maximally sensitive to short wavelength radiation (blue light) and minimally sensitive to long wavelength radiation (yellow and red).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is suggested that to obtain more beneficial effects, light must be turned on no earlier than the autumn equinox, and turned off not later than the spring equinox [48]. To minimize the potential bias from differences in daylight exposure, some authors recommended equally distributing treatment and placebo conditions across seasons [56, 64]. Another relevant aspect is the setting in which the light intervention is delivered and the modality of light exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Sloane et al [69] showed a statistically significant improvement in nighttime sleep with morning or all-day light (>2500 lux at the cornea), with greater improvement among persons with severe dementia. The authors claim that the effect size was greater than has been reported using prescription sleep medicines in long-term care populations.…”
Section: Review Figueiromentioning
confidence: 99%